Unified constitutive modeling for hot tensile behavior of TC4 alloy with and without diffusion bonding joint - Zhongman Cai; Yong Li; Yanqiang Xu; Jiarui Chen; Xiaoxing Li; Guanglu Ma; Dongsheng Li (Journal of Materials Research and Technology)
The hot deformation and fracture behavior of TC4 with and without diffusion bonding (DB) are investigated in both experimental and numerical methods in this study. The hot tensile tests of TC4 specimens with and without DB have been carried out at a temperature of 750 °C and strain rate of 0.1–0.0001 s−1, and the corresponding microstructure and fracture morphology under different deformation conditions have been analyzed by scanning electron microscope (SEM) and electron back scatter diffraction (EBSD). Straight grain boundaries, fine dynamic recrystallization (DRX) grains and weak joints formed by the DB process, which lead to lower stress and fracture strain than those of base metal (BM) specimens. Based on the experimental results, a new unified constitutive model considering the weld-dependent fracture coefficients and internal variables is developed, which can accurately predict the hot deformation and fracture behavior of TC4 with and without DB, describing the influence behavior of DB interface on hot deformation, as well as the evolutions of internal variables, including dislocation density, reserve fraction, DRX fraction and damage. The constitutive model has been further applied to the finite element method (FEM), and the prediction ability of the deformation behavior and the fracture of the model for hot deformation processes have been verified. It provides a theoretical basis for further accurate simulation of the hot forming of titanium alloy with DB.